From Policy to Practice: How Teachers Interpret Curriculum Levels in Indonesian TEFL Contexts - Bianca Aalya Frhasty; Meisarah Winertah; Bayu Santoso; Kalayo Hasibuan (MAN 4 Kota Pekanbaru, 2025)
This paper synthesizes findings from prior studies that investigate English teachers’ perceptions and practices in implementing English curriculum policies for Teaching English as a Foreign Language (TEFL) in Indonesian classrooms. A total of 25 national and international research articles published between 2013 and 2025 were reviewed to describe how teachers understand curriculum policy, respond to curriculum change, and engage in continuous professional development. The review also explores challenges teachers face and strategies they employ when translating curriculum documents into classroom practices. The analysis identifies four recurring themes: (1) varied perceptions of curriculum policy documents, (2) gaps between conceptual understanding and classroom implementation, (3) the influence of teacher competence on curriculum enactment, and (4) forms of resistance and constraints that limit teachers’ awareness and adoption of curriculum guidelines. Overall, the findings highlight the critical role of teacher knowledge, competence, and institutional support in shaping curriculum implementation across classroom contexts, and suggest the need for more sustained professional development aligned with actual teaching realities.